Morfem Derivasional dalam Bahasa Mandarin - Chandra, Yulie Neila (UI Scholars Hub, 2012)
Affixation is one of the process of morphological in Mandarin. Affixes are bound morphemes that are added to other morphemes to form larger units such as words, especially to form a compound word (成词 héchéng cí). Mandarin has two types of affixes: prefixes (precedes the morpheme) and suffixes (follows the morpheme). Prefixes are rare in Mandarin, such as 初chū-, 第dì-, 非fēi-, 可kĕ-, etc; while suffixes are more numerous, such as 儿-er, 化 –huā, 家 –jiā, 们 –men, 员 –yuán, 者 –zhĕ, 子-zi, etc. In Mandarin, affix morphemes can also be divided into two functional categories, namely inflectional morphemes and derivational morphemes, both refers two principal word formation processes: inflection and derivation. Although, Mandarin is not the inflection language, only prefix 初chū- and suffix 们–men are inflectional morphemes. Therefore, the derivation process is more productive in Mandarin. Derivational morphemes form new words by changing the meaning of the base (root) and the word class. In consequence, derivation in Mandarin may cause a change of word classes; such as nouns, verbs, and adjective, but generally form nouns.